Real-world evidence of chemotherapy effects in advanced pancreatic ductal adenocarcinoma: prognostic significance of TP53 status in gemcitabine plus nab-paclitaxel therapy - M. Sugimori; A. Hirotani; H. Yamazaki; M. Oshi; K. Kawashima; H. Tsuchiya; Y. Kanemaru; Y. Suzuki; S. Onodera; H. Miwa; A. Nozaki; K. Sugimori; et al. (ESMO Gastrointestinal Oncology)
Background: Gemcitabine plus nab-paclitaxel (GnP) and FOLFIRINOX (FFX) therapies are widely used to treat advanced pancreatic ductal adenocarcinoma (PDAC). This study aimed to identify the prognostic factors associated with these regimens, focusing on key genomic alterations in the ‘Big Four’ genes (KRAS, TP53, CDKN2A, and SMAD4). Materials and methods: This retrospective observational study analysed real-world data from 5205 PDAC patients registered in the national database, Center for Cancer Genomics and Advanced Therapeutics (C-CAT), who underwent comprehensive genomic profiling between June 2019 and December 2023 in Japan. Clinical characteristics and genomic alterations were analysed. Time to progression (TTP) was compared between patients treated with GnP or FFX as first-line therapy. Gene alterations were classified as truncating or missense mutations to assess prognostic relevance. Results: GnP was more frequently selected than FFX as first-line treatment (2315 versus 1181). FFX was more commonly used in younger, male patients without prior adjuvant therapy. After matching for age, sex, and adjuvant history, GnP demonstrated superior TTP compared with FFX (median TTP: 6.0 versus 5.5 months, P = 0.019). In the GnP group, TP53 alterations were associated with significantly shorter TTP compared with wild-type TP53 (median TTP: 5.8 versus 7.0 months; P < 0.0001). Furthermore, truncating TP53 mutations were linked to shorter TTP than missense mutations (median TTP: 5.3 versus 5.9 months; P = 0.021). Conclusions: In Japanese real-world data, GnP showed superior TTP compared with FFX for advanced PDAC. TP53 status may serve as a prognostic biomarker in patients receiving GnP therapy.